Ameliorative Effect of Pongamia Pinnata on Histopathology of Vital Organs Involved in the Alloxan Induced Diabetic Rats. Issue 2 (3rd April 2023) - Morajkar, Abhay; Sharma, Bharatbhushan; Kharat, Kiran
ABSTRACT: The ameliorative effect of aqueous (PPAqExt) and alcohol (PPAlcExt) extracts of Pongamia pinnata on degenerative histopathological changes in diabetic rats were investigated. Rats were divided into six groups. 1. Control group (NC). 2. Diabetic control group (DC)3. PPAqExt (TD1) 4. PPAlcExt (TD2) 5. Standard Control group (SD) 6. Vehicle Control group (VC). Blood samples were collected for the detection of Glycosylated Hemoglobin (HbA1c) levels. The vital organs pancreas, liver, kidney, and testis were prepared for histopathological studies. Treatment with PPAlcExt produced a reduction in HbA1c levels (8.4%) compared to DC (13.63%). The histopathological microscopic examination of diabetic rats showed marked changes in all the vital organs ranging from mild to severe along with cell infiltration, degeneration, and necrosis. Treatment with both the extracts showed a reversal in structural and cellular integrity of the vital organs involved in the pathophysiology of diabetes mellitus.